Power Relations and Gender Critique: Uncovering the Politics of Canonization in the Hadith of Al-Syu'm (Misfortune) - Irfan Fauzi; Hilal Askary Syirwan (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2026)
Theological stigmatization positioning women as objects of misfortune (bad omen) remains deeply entrenched due to the dominance of textual hadith readings that contradict Aisyah’s contextual correction. Unlike previous research, which has primarily focused on sanad criticism, this study addresses a scholarly gap by highlighting the politics of memory. Employing an interdisciplinary approach drawing on Foucault, Mernissi, and Gadamer and utilizing library research methods, this study aims to deconstruct the power relations underlying the canonization of the hadith in question. The findings reveal that the marginalization of Aisyah’s narrative is not a historical coincidence, but the product of a patriarchal epistemological hegemony that domesticates female intellectual authority to preserve the integrity of male narrators. In conclusion, the validity of misogynistic hadiths in the contemporary era cannot be established solely through sanad continuity; instead, they must be critically examined through the lens of matan content and the Tawhid paradigm to restore women as dignified subjects rather than sources of misfortune.